ELASTICITY SERVICE SAVING AND LOAN TO NET INCOME - Rahayu, Sri (PERMANA, 2011)
This Research aim to to know how big saving and loan service contribution to net income and to know how sensitivity storey;level ( saving and loan service elastisitas) to net income. From result of data analysis obtained [by] result of that result of calculation of SHU KUD Wanasari of year 2007 up to year 2010, tending to downhill because from year to year happened degradation of amount of SHU. Make-Up of the amount of SHU only happened from year 2007 to year 2008 equal to 2,1% caused by the existence of cost-saving, year 2008 to year 2009 downhill equal to 31,1% caused by abstracting of kerosene subsidize and changed with LPG, year 2009 to year 2010 downhill equal to 91,1% caused by some business unit lost ground. Service saving and loan contribution to year net income 2007 - 2010 reaching mean storey;level 55,65%, its meaning [of] saving and loan service contribution to big enough because more than 50 %. From result of calculation of elasticity can be obtained [by] saving and loan service elasticity storey;level to mean net income equal to - 2,8 % or number of inelastic because smaller than 1 (< 1). highest Elasticity storey;level in the year 2008 that is equal to 10,18 %, and while lowered in the year 2009 that is - 25,20 % ( reaching the condition of inelastis). So that as a whole if seen from mean can be expressed that sensitivity storey;level or influence of saving and loan service to net income not yet elastic ( inelastic)